BPM 2.0: Business Process Management meets Empowerment - Kurz, Matthias; Fleischmann, Albert (S-BPM ONE 2010, 2011)
Traditional approaches for business process management assume that process models remain unchanged. However, businesses today have to adapt their business process models to new market changes instantaneously. Current methods for business process management approaches and their supporting information systems turn out to be too time-consuming and costly. This contribution suggests a new business process management concept (BPM 2.0) along with a corresponding software system that increase the flexibility of businesses by allowing employees to improve "their" business processes. A case study at a large European construction firm critically examines the feasibility both of the concept as well as the software system. © 2011 Springer-Verlag.
WiSo2-Import:2015-10-02:508
Keywords: BPM 2.0; Business Processes; Empowerment; Enterprise 2.0; Web 2.0